(untitled) (Development Service Industry Management, 2025)
Іn today’s highly competitive market conditions, this article explores brand strategy as a key tool for ensuring the sustainable development of a company. The relevance of building a strong brand that contributes to increased recognition, fostering consumer trust, expanding market share, and enhancing the financial stability of the business is emphasized as crucial. The main elements of a brand strategy are examined, including: the brand concept as the foundation of the company’s identity, a unique selling proposition (USP) that creates competitive advantages, and the brand matrix or Jobs Story, which defines how a product or service meets consumer needs. Particular attention is paid to the importance of brand archetypes and tone of voice in developing an effective communication style that aligns with the target audience’s expectations. Additionally, the communication strategy is explored as a tool for promoting and supporting the brand in the market through various communication channels. The practical experience of successful Ukrainian brands that effectively implement a comprehensive approach to brand strategy development is analyzed. The article identifies the main challenges companies face when implementing a brand strategy and outlines possible ways to overcome them. These challenges include the need to adapt to rapid market changes, ensure brand consistency across all customer touchpoints, and effectively utilize digital communication channels. The conclusion highlights the importance of a strategic approach to brand management for ensuring the company’s long-term success, increasing its market value, and enhancing consumer loyalty. A brand strategy that considers all aspects of identity and communication becomes an integral part of the overall business development strategy.